The Imperative of Legal Research for Sustainable Development - Falade, Femi David; Oyewole, Oriola O. (ABUAD Law Journal, 2025)
The universe is governed by law, and so is nature and the inhabitants therein. Nature has a way of recreation and self-sustainability to a large extent. It could however give way to pressure by certain external and/or internal forces. Man, is one of the major sources of depletion or cause of imbalance in natural resources. While humans rely on available natural resources for survival, growth, and development, the effect of utilizing and pressuring these resources now, could have on the sustainability of future generations, cannot be underrated. Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Without any law regulating human activities, the arbitrary and uncontrolled utilization of natural resources could hinder present and future human sustenance. Legal research is a tool that can determine the appropriate legislation to control human activities concerning natural resources, vis-à-vis sustainable development. Adopting a black letter methodology, this paper aims to discuss the importance of legal research to sustainable development. The paper finds that legal research, if well conducted and articulated helps the policy or law makers to come up with laws and policies that will be acceptable to the members of the society with massive compliance and less need for enforcement.